“Efectos de microorganismos eficaces (em) en la producción de plantones de teca (tectona grandis) sector venecia-Banda de Shilcayo” - Hermoza Flores, Jean Paul (2016)
The present work of investigation named EFFECTS OF EFFECTIVE MICROORGANISMS (EM) IN THE PRODUCTION OF GRAFTS OF TECA (Tectana grandis) SECTOR VENICE- BAND OF SHILCAYO" Which hadas aims "evaluate and to compare the effect of the product known as effective microorganisms (EM) To different concentrations of application to foliate on the growth and production in fish pond of the Teca (Tectana grandis)", To determine the most efficient dose of EM, for the development of the plantulas of Teca (Tectana grandis). The present study, lt was realized in the zone of the Band of Shilcayo, Located in the sector Lagoon Venice, lt is characterized ecologically as a dry tropical forest, The temperature changes between 28 and 34º C, the relative dampness of 78,5 % and the average rainfall of 1147.8 mm. In the present work of investigation the Design of Blocks was used completely at random (DBCA), with seven (7) Treatments and three (3) repetitions, of which six (6), Treatments were applied different doses of effective microorganisms (EM) and (01) Treatment witness, supporting the same density of sowing in all the treatments, using in total 21 experimental units, the treatments T5 (8 cm3/4 liter of water of EM-Fos), T3 (6 cm3/4 liter of water of EM-Fos), T4 (7 cm3/4 liter of water of EM-Fos) y T2 (5 cm3/4 liter of water of EM-Fos) with averages of 31.47 cm, 29.40 cm, 29.40 cm and 28.80 cm respectively they were those who reached the highest averages for the height of plant.